2012
DOI: 10.1371/journal.pone.0049742
|View full text |Cite
|
Sign up to set email alerts
|

MR Neurography in Ulnar Neuropathy as Surrogate Parameter for the Presence of Disseminated Neuropathy

Abstract: PurposePatients with ulnar neuropathy of unclear etiology occasionally present with lesion extension from elbow to upper arm level on MRI. This study investigated whether MRI thereby distinguishes multifocal neuropathy from focal-compressive neuropathy at the elbow.MethodsThis prospective study was approved by the institutional ethics committee and written informed consent was obtained from all participants. 122 patients with ulnar mononeuropathy of undetermined localization and etiology by clinical and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…In addition, neuropathy of the upper extremity can have severe debilitating effects that account for the high morbidity of the disease. 7,34 Diagnosis remains a challenge and is mainly based on clinical and electrophysiological signs, the latter being particularly difficult to be performed and evaluated at proximal extremity sites. We hypothesized that MRN and specifically DTI could be an additional diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, neuropathy of the upper extremity can have severe debilitating effects that account for the high morbidity of the disease. 7,34 Diagnosis remains a challenge and is mainly based on clinical and electrophysiological signs, the latter being particularly difficult to be performed and evaluated at proximal extremity sites. We hypothesized that MRN and specifically DTI could be an additional diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…3 In imaging studies, T2-weighted (T2-w) imaging is currently the criterion standard for lesion detection and allows the assessment of spatial distribution and severity with good sensitivity and specificity. 2,3,7 Recent developments of MRN include more sophisticated "functional" imaging methods that allow the assessment, for example, of the blood-nerve barrier and nerve perfusion imaging in vivo. 11 Diffusion tensor imaging (DTI) offers another innovative approach to probe the cellular pathophysiology of disease and microstructural alterations on fiber level.…”
mentioning
confidence: 99%
“…18 Diagnostic accuracy of MRN has been widely reported in literature. 8,[19][20][21] However, studies demonstrating the impact on clinical management and patient outcomes are limited. Andreisek et al 22 found moderate to major impact in the evaluation of the majority of upper extremity neuropathies (84%) with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Even in 2006, Andreisek et al [27] found that the sensitivity and specificity of MR signs in CTS are low, and stated PNS disorders [16][17][18][19][20][21]. To achieve high structural resolution and visualization of nerve fascicles, high magnetic field strength of 3 T and fat-saturated 2D T2w sequences with an in-plane resolution of 0.1-0.4 × 0.1-0.4 mm and a slice thickness of 2-3.5 mm are required [21].…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%
“…We will focus on findings of MRN in the most frequent entrapment neuropathies as examples for focal nerve lesions, and on distally-symmetric level as surrogate parameter for disseminated neuropathies [19].…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%